2016
DOI: 10.1093/mnras/stw095
|View full text |Cite
|
Sign up to set email alerts
|

X-ray spectral studies of TeV γ-ray emitting blazars

Abstract: This work is a summary of the X-ray spectral studies of 29 TeV γ-ray emitting blazars observed with Swift/XRT especially focusing on sources for which X-ray regime allows to study the low and the high energy ends of the particle distributions function. Variability studies require simultaneous coverage, ideally sampling different flux states of each source. This is achieved using X-ray observations by disentangling the high-energy end of the synchrotron emission and the low-energy end of the Compton emission, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 172 publications
(150 reference statements)
5
35
0
1
Order By: Relevance
“…The results are consistent with the previous studies where for LSPs and ISPs, flatter X-ray spectral slopes varying between 1.5-2 are found (e.g. Donato et al 2005;Massaro et al 2008;Wierzcholska & Wagner 2016).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The results are consistent with the previous studies where for LSPs and ISPs, flatter X-ray spectral slopes varying between 1.5-2 are found (e.g. Donato et al 2005;Massaro et al 2008;Wierzcholska & Wagner 2016).…”
Section: Discussionsupporting
confidence: 93%
“…Raiteri et al (2009) analyzed the XMM−Newton observations of this source during the period 2007-2008 in its low state and found significant concave curvature in all of the observations. Wierzcholska & Wagner (2016) also found the signature of negative curvature in the BL Lac spectrum and found the break energy at ∼1.1 keV. We analyzed three pointings of XMM−Newton and found that the spectra shows an upturn at the break energy of around ∼1.25-1.55 keV.…”
Section: S4 0954+65mentioning
confidence: 78%
See 3 more Smart Citations